Electro-optical characteristics of an innovative LED luminaire with an LED matrix cooling system based on heat pipes - Pekur, D.V.; Sorokin, V.M.; Nikolaenko, Yu.E.; Kostylyov, V.P.; Solntsev, V.S.; Ponomarenko, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2020)
Widespread use of energy-saving LED lighting systems powered by renewable energy sources, solar energy in particular, will contribute to the improvement of global ecology. One of the structural elements of such lighting systems is an LED luminaire. The authors of this article perform a first-ever experimental study of the electro-optical characteristics of the basic version of a compact high-power LED luminaire for indoor use. The particular feature of this lighting device is that its cooling system for the LED light source is based on heat pipes and concentric cooling rings. Such a design allows ensuring the required cooling efficiency of the LED matrix. The revealed trends in optical and electrical parameters during temperature stabilization indicate that the proposed cooling system is highly efficient in maintaining normal thermal conditions of LED light sources with a power of up to 140.7 W and a luminous flux of up to 15083 lm. The results of determining the spatial distribution of luminous flux of these luminaires indicate that they may be used for lighting large rooms with high ceilings. Scaling the basic modular design version of the cooling system allows increasing the power of the LED light source up to 600 W. Покращенню екологічної ситуації в світі сприятиме широке використання енергоощадних світлодіодних систем освітлення із залученням для їх електроживлення поновлюваних джерел енергії, зокрема сонячної. Одним із структурних елементів такої системи освітлення є світлодіодний освітлювальний прилад. У даній роботі вперше проведено експериментальне дослідження електрооптичних характеристик базового варіанта компактного потужного світлодіодного освітлювального приладу для внутрішнього освітлення приміщень. Особливістю освітлювального приладу є те, що система охолодження світлодіодного джерела світла реалізована на основі теплових труб та концентричних кілець охолодження, що дозволило забезпечити достатню ефективність охолодження світлодіодної матриці. Виявлена динаміка зміни оптичних та електричних параметрів під час температурної стабілізації свідчить про високу ефективність запропонованої системи охолодження у забезпеченні нормального теплового режиму світлодіодного джерела світла при електричній потужності до 140,7 Вт та світловому потоці 15083 лм. Результати визначення просторового розподілу світлового потоку освітлювального приладу вказують на можливість його використання для освітлення приміщень з великими площами та висотою стелі. Масштабування базового варіанта модульної конструкції системи охолодження дозволяє підвищити потужність світлодіодного джерела світла до 600 Вт.